2012
DOI: 10.1258/jtt.2012.111002
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of diabetes self-management applications for Android smartphones

Abstract: We reviewed diabetes apps for Android smartphones. We compiled a list of free and paid apps in April 2011 by searching the Android Market for apps which could track self-monitoring of blood glucose (SMBG), diabetes medications or calculate prandial insulin dosages. Two reviewers independently evaluated six features per app, using a five-point Likert scale. The sum of the six ratings was the composite usability score, and the mean score of an app's features was the average usability score. Of the 80 Android dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
98
1
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(113 citation statements)
references
References 13 publications
9
98
1
5
Order By: Relevance
“…17 In addition, studies have identified mobile health app usability barriers for older patients. 18 While researchers have evaluated the usability of diabetes apps themselves, [19][20][21] there have been very few studies that have examined the usability of commercially available mobile apps among end-users-especially among a predominantly lower income patient population.…”
Section: Introductionmentioning
confidence: 99%
“…17 In addition, studies have identified mobile health app usability barriers for older patients. 18 While researchers have evaluated the usability of diabetes apps themselves, [19][20][21] there have been very few studies that have examined the usability of commercially available mobile apps among end-users-especially among a predominantly lower income patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Demidowich et al found that only 4 of 42 Android apps targeted towards diabetes self-management had sufficiently high composite usability scores, which suggested that few apps provided a comprehensive method of diabetes management. [39] In the current study, only 7 apps had overall quality scores ≥19 of 28, and only 5 met the best practices criteria. Our adapted HON quality score results are similar to that of Huckvale et al, who found generally low quality of asthma self-management apps using the HON criteria.…”
Section: Comparison With Prior Workmentioning
confidence: 63%
“…[29] In our data, it appeared as though user star ratings may be helpful to identify a quality app, but this data is not robust and others have found poor correlation between user-star ratings and app usability scores. [39] The current study found only 12 apps that contained any sort of educational component, with no app scoring above 50% for educational quality. This demonstrates that these apps were primarily designed to be tracking tools, with little emphasis on comprehensive, high quality educational material.…”
Section: Comparison With Prior Workmentioning
confidence: 63%
“…También, respecto a la edad, se ha indicado que conforme esta incrementa, las habilidades físicas y cognitivas disminuyen, tales como la agudeza visual, la detección del contraste y la escucha, además los pacientes diabéticos mayores pueden sufrir de complicaciones como retinopatía (10), por lo cual, lo mencionado por los participantes acerca de que las apps para el control de la diabetes deben ser sencillas, con interfaces intuitivas y con botones grandes y visibles, son puntos que se deben tomar en cuenta en el diseño de estas herramientas para este tipo de pacientes que pueden llegar a padecer retinopatía y neuropatía periférica (22).…”
Section: Discussionunclassified